2015
DOI: 10.3109/21678421.2014.999791
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic costs of amyotrophic lateral sclerosis according to staging system

Abstract: The objective of this study was to compare the cost of illness of amyotrophic lateral sclerosis (ALS) in the Korean population based on the staging system for ALS from the perspective of both patients and the government. Direct medical costs, care-related costs, and loss of productivity in patients with ALS were measured based on medical records and face-to-face interviews. The patients were divided into groups according to the staging system for ALS, and the cost of illness was analysed. A total of 151 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 17 publications
1
37
1
1
Order By: Relevance
“…Higher health and social care costs were associated with the use of non-invasive ventilation and gastrostomy and with shorter survival. Depending on the health care system in question, out-of-pocket expenses can also be substantial in ALS care 60,61…”
Section: Introductionmentioning
confidence: 99%
“…Higher health and social care costs were associated with the use of non-invasive ventilation and gastrostomy and with shorter survival. Depending on the health care system in question, out-of-pocket expenses can also be substantial in ALS care 60,61…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Denmark, Jennum et al (14) also found costs were highest in the index month, sharply rising during the months before diagnosis. Other ex-U.S. studies have found ALS costs increase with disease severity (4)(5)(6)(7)(8) and have connected rising costs to characteristics of disease progression such as wheelchairs and ventilators (4,5,8). However, the actual costs associated with ALS and when or how they are distributed across disease progression vary, indicating that the cost of ALS is multifactorial and likely to be dependent on country-specific healthcare policies.…”
Section: Discussionmentioning
confidence: 99%
“…substantial out-of-pocket expenses) on ALS patients (12). Moreover, cost and ALS disease severity relationships have been studied in Spain (5), the Netherlands (8), the United Kingdom (6), Denmark (14) and Korea (7), and most found that costs increased with disease severity across the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ALS staging methods have been proposed, with uses such as a tool for rehabilitation (3), rapid functional assessment (4), comparison of different treatment models (5,6), biomarker analysis (7) and health economics (8). The El Escorial criteria (9) provide a set of diagnostic guidelines that are based on patterns of disease spread but are not in themselves a staging system.…”
Section: Introductionmentioning
confidence: 99%